Synthesis and Characterization of Ca2Al2SiO7:Pr3+ Photoluminescence Materials via Sol-Gel Method - Maura Vanessa; Nirwan Susianto; Aep Patah (Jurnal Kartika Kimia, 2026)
Ca2Al2SiO7:Pr3+ is a potential UV-C-emitting material due to its photoluminescence properties. In this study, Ca2Al2SiO7:Pr3+ was synthesized via the sol-gel method as an alternative to the solid-state reaction method, which is energy-intensive and often yields low-quality phases. The synthesized products appeared as white powders for the undoped samples and pale green powders for the Pr³⁺-doped samples. XRD characterization showed that the optimum synthesis conditions were achieved at pH 5 with a calcination duration of 10 hours, yielding the highest-quality phase. Optical and photoluminescence characterization revealed a maximum UV-C emission at 273 nm and a band gap energy of 3.92 eV at a Pr³⁺ doping concentration of 7.25% moles.